Application and research progress of synthetic lethality in the development of anticancer therapeutic drugs - Gong, Xiaoliang; Liu, Chunxi; Tang, Haoyang; Wu, Song; Yang, Qingyun (Frontiers in Oncology, 2024)
With the tremendous success of the PARP inhibitor olaparib in clinical practice, synthetic lethality has become an important field for the discovery and development of anticancer drugs. More and more synthetic lethality targets have been discovered with the rapid development of biotechnology in recent years. Currently, many drug candidates that were designed and developed on the basis of the concept of synthetic lethality have entered clinical trials. Taking representative synthetic lethal targets Poly ADP-ribose polymerase 1 (PARP1), Werner syndrome helicase (WRN) and protein arginine methyltransferase 5 (PRMT5) as examples, this article briefly discusses the application and research progress of synthetic lethality in the development of anticancer drugs.